Heat stress maps for pigs in Uganda - CGIAR Research Program on Livestock (2020)
The heat stress maps were discussed with stakeholders, implications discussed, potential policy and farm-level actions discussed. The insights from this multi-stakeholder workshop fed in a policy brief and briefing